Vaccínia bovina, uma infecção sistêmica: evidencia de eliminação nas fezes, viremia e detecção do vírus em órgãos linfóides - Rivetti Junior, A. V.; Guedes, M. I. M. C.; Oliveira, T. M. L.; Rehfeld, I. S.; Matos, A. C. D.; Rodrigues, N. F. S.; Abrahão, J. S.; Kroon, E. G.; Lobato, Z. I. P. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2011)
Bovine vaccinia (BV) is an occupational zoonosis caused by Vaccinia virus (VACV), which affects dairy cattle and milkers. In bovine natural infections, it seems that BV is a localized disease, with cutaneous lesions restricted to the teats. However, there are no studies about experimental infection with VACV in bovines to establish its pathogenesis and elimination pathways. The aim of this study was to study the occurrence of viremia and elimination of VACV in bovine feces. Eight crossbred lactating cows, serologically negative for VACV, were used. Teats were previously scarified with sand paper and then inoculated with 106 pfu/100 μL of Guarani P2 (GP2) strain of VACV. Blood samples and feces were collected daily throughout the experiment. After 66 days post inoculation (d.p.i) the animals were divided into two groups that receive two new different treatments. One group was re-inoculated with the same inoculum and the other was subjected to chemical immunosuppression, to evaluate whether re-infected animals and/or experimentally infected animals that recover from previous lesions in conditions of immunosuppression could eliminate VACV on feces once more. Animals from both groups were monitored for up the 89th day post initial inoculation. Viral DNA was continuously detected and quantified in blood and feces of these animals in an intermittent way, even after the resolution of the lesions. At slaughter, tissues were collected and the viral DNA was detected and quantified from mesenteric and retro mammary lymph nodes, ileum, spleen and liver. The detection of VACV DNA in blood and feces for long period and its detection in lymphatic organs provide new evidence about VACV elimination and suggest, for the first time, that BV could be a persistent systemic infection.